(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe image of the soldier, as a hero who sacrifices everything to defend hiscountry and values, is no longer depicted in modern drama. With two World Warsand many regional wars and civil wars, the soldier becomes a victim, not a hero.Authors present the character of the soldier as a man who suffers a lot as he isvictimized by his own government and its politics that forces him to be in such aposition. Dramatists express their views about race, oppression and war throughtheir characters, such as the character of the soldier, as in the two selected plays forthis research: The Hostage by Brendan Behan and A Soldier’s Play by CharlesFuller.The Hostage depicts, through its events, the Irish oppression which makesboth the Irish and the English victims for this conflict. A Soldier’s Play presents theoppression which the blacks face daily in their society, a matter which createsamong them the oppressed and the oppressor.An oppressed people demand that all their resources be put to theservice of liberating them, no matter what these resources are. Certainly art andculture must be seen in such a light. Literature, as part of art is sometimes themirror of its society and people. Dramatists, in general, and Brendan Behan andCharles Fuller, in particular, are aware of the value of the theatre as a tool for socialdiscussion, therefore; their characters no more assume limited quality, as theyassume a universal one.1Berndan Behan’s The Hostage, which lies in three acts, was firstpresented by Theatre Workshop in 1958. It takes place in an old house in Dublin. Itis owned by Monsewer, an Englishman by birth, who is more fanatically Irish thanhis entourage; Pat, who served with Monsewer in the civil war, is no longer fanatic.